Isolation and Utilization of Toxins from Marine Invasive Species Towards the Management of Their Population - Papadaki, Sofia; Sofia, Pappou; Panagiotis, Dimou; Magdalini, Krokida (European Journal of Sustainable Development, 2022)
The pufferfish Lagocephalus sceleratus and lionfish Pterois miles, are two of the most important marine alien species of the Mediterranean basin. L.sceleratus is one of the most toxic species on the planet, as its tissues contain Tetradotoxin (TTX), a neuroparalytic toxin that can cause death if consumed, while lionfish is also venomous and causes a wide range of symptoms when its venom is injected through the hard thorns of its fins. Both species have rapidly developed large populations in the Eastern Mediterranean basin, while showing increasing signs of spread in the Central and Western part, causing a wide range of socioeconomic and environmental impacts. Finding innovative methods for their economic exploitation is a basic condition in order to create incentives for their targeted fishing and to achieve the limitation of their populations. A study was conducted on the isolation and identification techniques of toxins from both species. In the context of the utilization of the tetradotoxin (TTX) contained in L.sceleratus, an attempt was made to integrate it into products of high added value, such as cosmetics, after the study of its encapsulation in a polymer matrix through the electro-hydrodynamic process of electrospraying.